2020
DOI: 10.3389/fpls.2020.607174
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Genome Editing and Induced Excision of the Transgene in N. tabacum BY2 Cells

Abstract: While plant cells in suspension are becoming a popular platform for expressing biotherapeutic proteins, the need to pre-engineer these cells to better comply with their role as host cell lines is emerging. Heterologous DNA and selectable markers are used for transformation and genome editing designated to produce improved host cell lines for overexpression of recombinant proteins. The removal of these heterologous DNA and selectable markers, no longer needed, can be beneficial since they limit additional gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…This enables targeted overexpression or knockdown of genes associated with pivotal agroclimatic traits. Recent studies demonstrated a comparative analysis of using CRISPR/Cas9 system under a heat shock inducible promoter produces less off-target mutations compared to constitutive ubiquitin promoter in Arabidopsis, rice, and tobacco (Liang et al, 2023; Nandy et al, 2019; Sheva et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This enables targeted overexpression or knockdown of genes associated with pivotal agroclimatic traits. Recent studies demonstrated a comparative analysis of using CRISPR/Cas9 system under a heat shock inducible promoter produces less off-target mutations compared to constitutive ubiquitin promoter in Arabidopsis, rice, and tobacco (Liang et al, 2023; Nandy et al, 2019; Sheva et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the constitutive rice ( Oryza sativa ) UBIQUITIN promoter, the use of the heat‐inducible heat‐shock protein 17.5E promoter from soybean ( Glycine max ) resulted in much fewer off‐target effects when used to express Cas9 (Nandy et al., 2019). Likewise, the Arabidopsis heat‐shock protein 18.2 ( HSP18.2) promoter was used to express a specific sgRNA targeting the T‐DNA boundaries for a transgene excision in a tobacco ( Nicotiana tabacum ) BY2 cell suspension (Sheva et al., 2020). The target efficiency, specificity, and programmability of IGE systems are dependent on the inducible strategies adopted.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, the CRISPR/Cas9 cassette is left in the genome, and further work is required to segregate the transgene from the mutations and thus generate transgene-free lines. [35,36 ] The workload becomes more difficult to manage for the introduction of multiple mutations, and ideally, it would be possible to introduce all mutations and remove the transgene cassette in the T0 and T1 generations, respectively. Fluorescent proteins can be used for the noninvasive confirmation of transgene removal, and this has been applied to CRISPR/Cas9 editing in many species.…”
mentioning
confidence: 99%